Enhancing Antitumor Immunity with Antiangiogenic Therapy: A Clinical Model in Renal Cell Carcinoma?. (29th April 2019) - Gao, Xin; McDermott, David F.; Michaelson, M. Dror
Abstract : Combination therapies involving antiangiogenic agents plus immune checkpoint inhibitors have recently demonstrated clinical efficacy in advanced renal cell carcinoma (RCC). This commentary summarizes the clinical advances and reviews the potential implications for RCC and other advanced solid tumors.